Peculiarities of Translation of Works of Fantasy Genre - Zarina, Isaxanova (International Journal on Integrated Education, 2023)
The article has made an attempt to analyse the peculiarities of fiction translation. The science-fiction text not only completely repeats the features of the fiction text, but also has a number of its own characteristics: the presence of a large number of occasional vocabulary, realities and proper names. The author reveals the translation transformations which have been used by the translator in order to transfer the structure and the vocabulary of the author's text as close as possible, while maintaining the adequacy and accessibility to the perception.